Pengaruh Leverage dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Tahun 2021 - Marcelline (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research analyzes and tests the impact of both leverage and company size on the financial performance of publicly listed healthcare sector companies (tbk.) on the Indonesia Stock Exchange (IDX) in the year 2021. The sample selected by the researcher consists of 28 out of the total 30 companies in Indonesia listed on the IDX, with the criteria being healthcare sector companies that issued annual financial reports in 2021. In conducting the analysis, the data collected by the researcher were tested using SPSS version 26. For data calculation, the researcher used the Debt to Asset Ratio to analyze leverage and the Ln of Total Assets to analyze company size. Additionally, the author also analyzed company performance using the Return on Asset (ROA) formula. The results of this research indicate that the utilization of leverage has a negative impact on the financial performance of companies in the healthcare sector. Nonetheless, the company's size did not show any notable effect on the financial performance of firms operating within the same industry. Keywords: Leverage, Company’s Size, Company’s Financial Performance.